1999
DOI: 10.1080/135765099396917
|View full text |Cite
|
Sign up to set email alerts
|

Handedness Effects on Playing a Reversed or Normal Keyboard

Abstract: A group of left-handers, approaching the piano for the first time, showed better performance in playing a reversed keyboard (where the pitch decreased from left to right) than a normal keyboard. By testing a separate group of``experienced' ' lefthanders, it was also found that this observed preference that naive left-handers had for the reversed keyboard can disappear with a few years of practice on a normal keyboard. The initial preference for the reversed keyboard shown by left-handers appeared to be specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
5
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Two-thirds of the time he played on reversed pianos, both for professional recordings and international performances. Laeng and Park (1999) compared the correctness of notes in piano playing of left-handed and right-handed amateurs, whose average keyboard training was two years, and novices. Subjects played simple scores (with a fast-moving melody in the right hand and a slow-moving accompaniment in the left hand) on a normal keyboard and inverted scores (with the fast-moving melody in the left hand) on a reversed keyboard.…”
mentioning
confidence: 99%
“…Two-thirds of the time he played on reversed pianos, both for professional recordings and international performances. Laeng and Park (1999) compared the correctness of notes in piano playing of left-handed and right-handed amateurs, whose average keyboard training was two years, and novices. Subjects played simple scores (with a fast-moving melody in the right hand and a slow-moving accompaniment in the left hand) on a normal keyboard and inverted scores (with the fast-moving melody in the left hand) on a reversed keyboard.…”
mentioning
confidence: 99%
“…At no point were participants presented with a visual representation of melodies, which may induce associations between pitch and space, particularly for pianists. Thus, we found more effective flexibility in this study than a similar study by Laeng and Park (1999), in which pianists and nonpianists (who could read music) exhibited difficulty learning melodies based on the same inverted mapping used here, but in a learning paradigm that relied on standard music notation. The second critical feature is the use of auditory feedback manipulations in the test phase.…”
Section: Discussionmentioning
confidence: 38%
“…Neuroimaging studies adopting a learning-by-ear paradigm have shown that nonpianists can form audiomotor associations based on musical training within 20 minutes, thus suggesting that standard mapping of pitch to space on a keyboard may be well-suited to sensorimotor learning (Bangert & Altenmüller 2003;Lahav, Saltzman, & Schlaug, 2007;Mutschler et al, 2007). In addition, a study in which nonpianists (who were also musicians) learned melodies on a normal keyboard or one in which the mapping of pitch to space was inverted (high pitch to the left, low pitch to the right) showed an advantage for normal pitch mapping, at least for right-handed participants (Laeng & Park, 1999). This result suggests that the standard right/high left/low space-topitch mapping may be well suited to the cerebral dominance of the larger portion of the population (Jäncke, 2002).…”
mentioning
confidence: 97%
“…The relationships identified between hand assignment, relative salience, and error rates in the Dorian fugue further point to a clear right-hand advantage, at least for righthanded performers. Whether by design or by accident, the frequency mapping of the keyboard takes into account both cognitive-motor and perceptual constraints of right-handed musicians by locating the higher, more salient frequencies on the right side; indeed, whereas naïve left-handers have been found to prefer keyboards with an inverted frequency mapping, right-handers prefer the normal configuration regardless of their musical experience (Laeng & Park, 1999).…”
Section: Discussionmentioning
confidence: 99%